Glazing daylighting performance and Trombe wall thermal performance of a modular façade system in four different Portuguese cities - Sacht, H. M. (2015)
This paper reports on a new façade system that uses passive solutions in the search for energy efficiency. The differentials are the versatility and flexibility of the modules, which are important advantages of the system. The thermal performance of Trombe walls and glazings and the daylighting performance of glazing were the key aspects analyzed in the results. Computational simulations were accomplished for the thermal performance of different arrangements of the modules with DesignBuilder software. The glazing daylighting performance was studied by means of Ecotect and Desktop Radiance programs and compared with the transmittance curves of glazings. Occupancy profile and internal gains were fixed according to the Portuguese reality for both studies. The main characteristics considered in this research were the use of two double glazings, four different climates in Portugal and one and two Trombe walls in the façade. The results show an important reduction in the energy consumption with the use of Trombe walls and double self-cleaning glazing in the façade, which also presented better daylighting performance.